Pengaruh Jenis Umpan Pancing Ulur Terhadap Hasil Tangkapan Ikan Kurisi (Nemipterus nematophorus) - Julius Mose Rahaningmas (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2020)
The fishing of kurisi fish (nemipterus nematophorus) using handline in Watdek waters Southeast Maluku district in November 2019. Types of anchovy bait (sardinella leiogaster) and tumel (dendronereis pinnaticirris) are used to catch kurisi fish. The fishing time is divided into two, namely at 07.00 – 10.00 a.m and at 14.00 – 17 p.m. The method used is a comparative descriptive analysis method to see the difference in the time of catching kurisi fish to the catching result and statistical analysis of a completely randomized design (CRD) to see the influence of the bait on the number of catching result. The total number of kurisi fish caught was 498. Tumel bait gets the most catches, 352 (71%), while anchovy bait only get 146 fish (29%). The most effective time for catching kurisi fish is at 07.00 a.m – 10.00 a.m, getting 349 fish (74%) and at 14.00 – 17.00 p.m get 123 fish (26%).